2003
DOI: 10.1017/s0022112002002653
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami run-up and draw-down on a plane beach

Abstract: Tsunami run-up and draw-down motions on a uniformly sloping beach are evaluated based on fully nonlinear shallow-water wave theory. The nonlinear equations of mass conservation and linear momentum are first transformed to a single linear hyperbolic equation. To solve the problem with arbitrary initial conditions, we apply the Fourier–Bessel transform, and inversion of the transform leads to the Green function representation. The solutions in the physical time and space domains are then obtained by numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
248
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(269 citation statements)
references
References 8 publications
11
248
1
4
Order By: Relevance
“…In the nonlinear theory the same effects can be found for a particular case of the linearly inclined bay with a parabolic cross-section m = 2 ). The solution of the nonlinear problem in this case can be obtained with the use of the Legendre (hodograph) transformation, which has been very popular for long wave runup on a plane beach (Carrier and Greenspan, 1958;Pedersen and Gjevik, 1983;Synolakis, 1987;Tadepalli and Synolakis, 1996;Li, 2000;Li and Raichlen, 2001;Carrier et al, 2003;Kânoğlu, 2004;Tinti and Tonini, 2005;Kânoğlu and Synolakis, 2006;Didenkulova et al, 2006;2008a;Antuono and Brocchini, 2007;Pritchard and Dickinson, 2007) and is valid for non-breaking waves. In this case the nonlinear system (3) can be reduced to the linear equation (Choi et al, 2008; …”
Section: Traveling Waves In U-shaped Bays With a Arbitrary Varying Dementioning
confidence: 99%
“…In the nonlinear theory the same effects can be found for a particular case of the linearly inclined bay with a parabolic cross-section m = 2 ). The solution of the nonlinear problem in this case can be obtained with the use of the Legendre (hodograph) transformation, which has been very popular for long wave runup on a plane beach (Carrier and Greenspan, 1958;Pedersen and Gjevik, 1983;Synolakis, 1987;Tadepalli and Synolakis, 1996;Li, 2000;Li and Raichlen, 2001;Carrier et al, 2003;Kânoğlu, 2004;Tinti and Tonini, 2005;Kânoğlu and Synolakis, 2006;Didenkulova et al, 2006;2008a;Antuono and Brocchini, 2007;Pritchard and Dickinson, 2007) and is valid for non-breaking waves. In this case the nonlinear system (3) can be reduced to the linear equation (Choi et al, 2008; …”
Section: Traveling Waves In U-shaped Bays With a Arbitrary Varying Dementioning
confidence: 99%
“…The benchmark reference data for this 2D runup problem was obtained from the analytical solution of NSW equations of Carrier et al [40], for the initial tsunami wave profile shown in Figure 5 (without initial velocity) and a given beach slope (1:10). The benchmark task was to compute the free surface elevation in the runup region at three points in time (t = 160, 175, 220 s) and to compare those to the reference solution.…”
Section: A 2d Tsunami Runup Over a Plane Beachmentioning
confidence: 99%
“…The viscosity for the given LB parameters in Figure 5a still is several orders of magnitude higher than the viscosity of water (ν ≈ 25 m 2 /s), but a further decrease does not significantly change the results. [40] (alternating dots and dashes) for three points in time.…”
Section: A 2d Tsunami Runup Over a Plane Beachmentioning
confidence: 99%
“…In this paper, we are concerned with the third phase, where the increasing effect of nonlinearity may lead to quite different outcomes, depending on the wave polarity as the wave transverses the deep ocean, see Carrier et al (2003) and Fernando et al (2008) for instance. Although initial depression waves are potentially just as damaging as initial elevation waves, they have not received the same attention, although we note the theoretical studies by Synolakis (1994, 1996), and most recently by Grimshaw et al (2015), the analysis of field data by Soloviev and Mazova (1994), and the experiments of Kobayashi and Lawrence (2004), Klettner et al (2012), Rossetto et al (2011) and Charvet et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the development of a tsunami as it approaches the shore have used the nonlinear shallow water equations to examine the connection between the incident wave mass, amplitude and polarity, on the shoreline impact, see for instance Synolakis (1994, 1996), Carrier et al (2003), Madsen and Schaffer (2010) and Didenkulova and Pelinovsky (2011). In particular, studies by Didenkulova (2009), Didenkulova et al (2006Didenkulova et al ( , 2007 and Pelinovsky (2006) using the nonlinear shallow water equations have elucidated the role of initial steepness in increasing the eventual run-up height, and we especially note that Didenkulova et al (2014) found that this nonlinear steepness effect was enhanced when the initial wave was one of depression.…”
Section: Introductionmentioning
confidence: 99%